Guaianolides from Ormenis mixta: Structural Insights and Evaluation of Their Anti-inflammatory Profile - Benteldjoune, Mounira; Chini, Maria Giovanna; Iannuzzi, Anna Maria; Kabouche, Ahmed; Kabouche, Zahia; DʼAmbola, Massimiliano; Marzocco, Stefania; Autore, Giuseppina; Bifulco, Giuseppe; De Tommasi, Nunziatina (Planta Medica, 2019)
In this paper, the isolation of five new guaianolides (1 – 5) and four (6 – 9) known sesquiterpenes from Ormenis mixta aerial parts is reported. The structural determination of the guaianolides was obtained by NMR spectroscopic data, as well as MS experiments. Their relative configurations were assigned by a combined quantum mechanical/NMR approach, comparing the experimental 13C/1H NMR chemical shift data and 1JH-H homonuclear coupling constants with the related predicted values. The isolates were assayed for their anti-inflammatory potential evaluating nitric oxide release and cyclooxygenase-2 expression in J774A.1 macrophages treated with lipopolysaccharide from Escherichia coli. Our results indicated that, among the tested compounds, 1 – 3, and 7 were able to inhibit nitric oxide release, while all were able to inhibit cyclooxygenase-2 expression with different potencies.
Keywords: Ormenis mixta; Asteraceae; sesquiterpenes; DFT/NMR approach; anti-inflammatory activity